A STUDY ON THE ABILITY OF THE STUDENTS IN COMPREHENDING RECOUNT TEXTS - Irma Aprillya; Supriusman Supriusman; Erni Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was conducted to find out the students’ ability incomprehending recount texts. This descriptive research design took place in SMP N 1Kuantan Hilir Seberang. The sample was 22 students from VIII2 class that wereselected by using cluster random sampling. There were 40 questions in this test. Theresearcher used the validity and reliability formula of theory Heaton 1991 in analysisdata by using manual calculation, it was found that the reliability of the test was 1.13which means that the reliability of the test was very high. The data were analyzed bycalculating the students’ score individually and finding out the mean score. Thestudents’ scores were classified into four ability levels; poor, mediocre, good, andexcellent. Based on the results of this research, the students’ ability in comprehendingrecount text at second year of SMP N 1 Kuantan Hilir Seberang was in good level.Meanwhile, the mean score of the whole students’ scores was 71.9. It was found that thehighest mean score is in finding social function and finding generic structure with themean score 75.4. The lowest aspect in comprehending recount text was in makinginferences with the mean score was 65.45.Key Words: Students’ Ability, Comprehending Recount Text